The dynamics of the math class mediated by communication - Jiménez-Espinosa, Alfonso (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This review article discusses how communication in a math class is understood. In this text, communication is more than reporting. It is the act of putting something in common until assigning meaning collectively, a process that enables the understanding and establishment of communicative relationships between subjects, with the purpose of giving joint meaning to what is communicated. It is also a strategic social interaction, where communicators create and modify their interpretations by the influence of the social context. This work shows that in the study of the dynamics of a mathematics class, names are used as communication categories, communication patterns, models, learning environments, spaces, classroom environments and interaction patterns, which describe the characteristics of the different forms of communication that are given in the classroom. From the verbal interaction, communication can have three different logics in the design of messages: expressive, conventional, and rhetorical. Depending on what logic an individual uses to communicate, his message is heard in a very different way. There seems to be a consensus that mathematics class where there is good communication would be one where students engage in the practice of a discourse called mathematics.